Socio-cultural influences in the composition of traditional Malay house compounds in rural Melaka - Ani, Anisa; Mohamed, Noorizan; Abdul Rahman, Nordin (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
The traditional Malay living environment is planned carefully through harmonious interactions between man, nature and culture, which are translated into the home design and the surroundings. However, rapid urbanization and industrialization in Malaysia have transformed many traditional villages due to the insufficient numbers of studies done in the local context. This paper explores the existence of the local essences of the Malay landscape characteristics within rural traditional residential gardens through the study on preferences and influencing factors. Eighteen case studies were involved in the quantitative and qualitative inventory processes in understanding the local context. Ian McHarg’s Overlay analysis was adopted in this study to correlate the data by using the macro and micro analyses in order to understand the preferences and influences within the social and cultural contexts. Significant characteristics emerged as the essences of Malay socio-cultural identity, which have been identified as desperately in need of immediate acts of conservation